1973
DOI: 10.1111/j.1467-6494.1973.tb00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality similarity and friendship choice: Similarity of what, when?1

Abstract: he theoretical and practical values of devotmg research efforts to the study of interpersonal attraction and fnendship formation have dictated that a diversity of studies would be earned out with a consequent identification of a large number of relevant factors (Berscheid & Walster, 1969, Byrne, 1969, Senn, 1971. Such findmgs might be expected to have a direct apphcation in the solution of a wide variety of problems associated with interpersonal relationships, such as identification of potentially effective wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 15 publications
3
31
1
Order By: Relevance
“…Instead, people who (claim to) possess traits traditionally associated with the other sex (i.e., high on cross-sex characteristics) tend to have more cross-sex friends. Such a result is in accord with the wellknown finding that similarity facilitates friendship formation more generally (Duck, 1973;Duck & Craig, 1978).…”
Section: Discussionsupporting
confidence: 93%
“…Instead, people who (claim to) possess traits traditionally associated with the other sex (i.e., high on cross-sex characteristics) tend to have more cross-sex friends. Such a result is in accord with the wellknown finding that similarity facilitates friendship formation more generally (Duck, 1973;Duck & Craig, 1978).…”
Section: Discussionsupporting
confidence: 93%
“…The similarity model of interpersonal behavior has found empirical support particularly in the field of interpersonal attraction. The similarity-attraction hypothesis (e.g., Duck 1973) suggests that similar personality characteristics are related to mutual attraction and liking (for an overview, see Dryer and Horowitz 1997). Moreover, research on emotions and nonverbal behavior has shown an assimilation or 'synchronization' of interaction behavior in the course of the interaction.…”
Section: The Role Of Interpersonal Behavior In Coaching Interaction Pmentioning
confidence: 97%
“…It has been observed in interpersonal contexts that positive evaluations of the outcomes of an interaction, in addition to fostering a desire for future interactions, lead to a desire to get better acquainted with the interaction partner (Duck 1973). Similarly, it has been demonstrated that beliefs an individual holds about his or her relationship with another affect how his or she chooses to interact with that person in the future (Byrne and Griffitt 1973).…”
Section: The Dynamic Component: the Effects Of Behavioral And Relatiomentioning
confidence: 99%